PENGARUH GOOD CORPORATE GOVERNANCE DAN LEVERAGE TERHADAP MANAJEMEN LABA - FIOREN ASITALIA; ITA TRISNAWATI (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2017)
The purpose of this study is to obtain empirical evidence about the influence of good corporate governance and leverage on earnings management. Good corporate governance in this study included managerial ownership, institutional ownership, board size, audit committee’s size, and the proportion of independent commissioners. This research used discretionary accrual as proxy of earnings management. The Samples of this research used 93 companies manufacturing sector which listed in Indonesia Stock Exchange during period 2013 to 2015, using purposive sampling method. This research used multiple regression to test the hypothesis. The result of this research showed that all component of the good corporate governance (manajerial ownership, institutional ownership, board size, audit committee’s size, and the proportion of independent commissioners) had no effect to earnings management, while leverage had a negative effect to earnings management.